EURAD State-of-the-Art Report: ACED assessment of the chemical evolution at the disposal cell scale—part I—processes at interfaces and evolution at disposal cell scale - Neeft, Erika; Deissmann, Guido; Jacques, Diederik (Frontiers in Nuclear Engineering, 2025)
Within the framework of the European Joint Programme on Radioactive Waste Management, the work package ACED -Assessment of chemical evolution of intermediate level (ILW) and high level (HLW) waste at disposal cell scale -uses combined experimental and modelling methods in a multiscale approach with process integration to improve the long-term modelling and assessment of the chemical evolution at the disposal cell scale. This work together with Part II gives a comprehensive overview of methods and approaches to combine knowledge and tools into numerical models that assess the long-term evolution. Part I provides the relevance of the assessment of the chemical evolution for safety, performance, and optimization. It further describes the main characteristics of disposal cells for ILW and HLW waste in European disposal programmes. From that, a number of interfaces between different types of material are identified that are highly relevant for many national disposal programs: glass-steel, steel-concrete, steel-clay, steel-granite, concrete-clay, and concretegranite. Based on literature review, the main processes and consequences occurring at these interfaces due to chemical gradients are described. The key element is the narrative of the general evolution at the disposal cell scale based on process knowledge.